"Pivoting" by food industry firms to cope with COVID‐19 in developing regions: E‐commerce and "copivoting" delivery intermediaries. (16th April 2021) - Reardon, Thomas; Heiman, Amir; Lu, Liang; Nuthalapati, Chandra S.R.; Vos, Rob; Zilberman, David
Abstract: Coronavirus disease 2019 and related lockdown policies in 2020 shocked food industry firms' supply chains in developing regions. Firms "pivoted" to e‐commerce to reach consumers and e‐procurement to reach processors and farmers. "Delivery intermediaries" copivoted with food firms to help them deliver and procure. This was crucial to the ability of the food firms to pivot. The pandemic was a "crucible" that induced this set of fast‐tracking innovations, accelerating the diffusion of e‐commerce and delivery intermediaries, and enabling food industry firms to redesign, at least temporarily, and perhaps for the long term, their supply chains to be more resilient, and to weather the pandemic, supply consumers, and contribute to food security. We present a theoretical model to explain these firm strategies, and then apply the framework to classify firms' practical strategies. We focus on cases in Asia and Latin America. Enabling policy and infrastructural conditions allowed firms to pivot and copivot fluidly.